Direct thrombus aspiration using the Penumbra system for the treatment of pediatric intracranial dissection. (16th November 2012) - Fujimoto, Motoaki; Tateshima, Satoshi; Ali, Latisha; Raychev, Radoslav; Vinuela, Fernando
Abstract : We describe a case of a 15-year-old girl who developed a spontaneous intracranial arterial dissection with distal middle cerebral artery (MCA) occlusions. From the digital subtraction angiography provided, the dissection flap appeared to originate at the internal carotid artery terminus with extension into the right M1 segment and occluding the right anterior cerebral artery, A1 segment. CT perfusion study showed salvageable tissue in the posterior MCA territory, including the motor cortex. In order to avoid further injury to the dissection, clot retrieval systems were not a treatment option. We therefore performed selective thrombus aspiration with the Penumbra system for the occluded central and precentral arteries distal to the non-occlusive dissecting lesion. Sufficient recanalization was achieved and the patient made a marked recovery. Although mechanical thrombectomy with the use of retrieval intracranial stent systems has demonstrated satisfactory recanalization rates, the aspiration methodology remains useful for patients with an accompanying proximal vascular lesion.